Pratuokng : The Borneo Bamboo Zither of Bidayuh Sarawak - Sinin, Hamdan; Khairul Anwar, Mohamad Said; Ahmad Faudzi, Musib; Md Rezaur, Rahman; Marini, Sawawi; Aaliyawani Ezzerin, Sinin (North Carolina State University, 2024)
The pratuokng is an idiochord tube zither, which is a musical instrument. The Bidayuh Biatah pratuokng bamboo sound radiators of Annah Rais in Padawan, Sarawak, Malaysia are made up of seven strings and one drum. The sound reproduction capabilities are unique and innovative. This study intends to highlight the importance of sound studies in the studio setting. The frequency spectrum was evaluated using a Fast Fourier Transform (FFT) analysis via PicoScope oscilloscopes, and the time frequency analysis (TFA) using Adobe Audition that produced the spectrograms. The observations and perceptions offered by the actual meaning of this bamboo tube zither instruments showed that the notes of the pratuokng strings are E, D, F, Ab, B, A#, and B, respectively. The drum note is A. The 1st, 2nd, 3rd(A), 3rd(B), 4th(A), 4th(B), and 5th strings are 320 Hz (E4 = 329.63), 300 Hz (D4 = 293.67), 350 Hz (F4 = 349), 410 Hz (A4b = 415), 490 Hz (B4 = 493), 470 Hz (A4# = 466), and 500 Hz (B4 = 493), respectively, i.e., with note E, D, F, Ab, B, A#, and B, respectively. The drum is 210 Hz (A3 = 220). The signal in the frequency spectrum showed both distinct fundamental and higher partial frequencies. In particular, the first octave are present except for string 4B and 5. The inconsistent number of partials in each string is due to the inconsistent thickness of the raised fiber from the bamboo tube.